AZEVEDO, Artur. O velho Lima - REA Editor (Revista Espaço Acadêmico, 2017)
Fonte: MAGALHÃES JÚNIOR, R. (Seleção e Notas) O Conto da Vida Burocrática. Rio de Janeiro, Editora Civilização Brasileira S. A., 1960, p. 37-42.